A New Methodology to Determine Apposition, Dilatation, and Position of Endografts in the Descending Thoracic Aorta After Thoracic Endovascular Aortic Repair. (October 2019) - van Noort, Kim; Schuurmann, Richte C. L.; Post Hospers, Gersom; van der Weijde, Emma; Smeenk, Hans G.; Heijmen, Robin H.; de Vries, Jean-Paul P. M.
Purpose: To validate computed tomography angiography (CTA)–applied software to assess apposition, dilatation, and position of endografts in the proximal and distal landing zones after thoracic endovascular aortic repair (TEVAR) of thoracic aortic aneurysm.Materials and Methods: Twenty-two patients (median age 75.5 years; 11 men) with a degenerative descending thoracic aortic aneurysm treated with TEVAR with at least one postoperative CTA were selected from a single center's database. New CTA-applied software was used to determine the available apposition surface in the proximal and distal landing zones, apposition of the endograft fabric with the aortic wall, shortest apposition length, endograft inflow and outflow diameters, shortest distance between the left subclavian artery and the proximal endograft fabric, and shortest distance between the celiac trunk and the distal endograft fabric on each CTA. Interobserver variability for these parameters was assessed with the repeatability coefficient and the intraclass correlation coefficient.Results: Excellent interobserver agreement was found for all measurements. Interobserver variability of surface and shortest apposition length calculations was larger for the distal site compared with the proximal site, with a mean difference of 10% vs 2% of the mean available apposition surface, 12% vs 5% of the endograft apposition surface, and 16% vs 8% of the shortest apposition length, respectively. Inflow and outflow diameters of the endograft showed low variability, with a mean difference of 0.1 mm with 95% of the interobserver difference within 1.8 mm. Mean interobserver differences of the proximal and distal shortest fabric distances were 1.0 and 0.9 mm (both 2% of the mean lengths).Conclusion: Assessment of apposition, dilatation, and position of the proximal and distal parts of an endograft in the descending thoracic aorta is feasible after TEVAR with the new software. Interobserver agreement for all measured parameters was excellent for the proximal and distal landing zones. The new method allows detection of subtle changes during follow-up. However, a larger study is needed to quantify how parameters change over time in complicated and uncomplicated TEVAR cases and to define the real added value of the new methodology.